EMIGRATION FROM UKRAINE AS A FACTOR AFFECTING THE STATE OF ITS BALANCE OF PAYMENTS - LYPKO, Nazarii (Journal of European Economy, 2025)
This study problematizes how emigration from Ukraine impacts the condition of its balance of payments. A comparative analysis was conducted to determine whether the patterns of international financial inflows from emigrants have changed since the outbreak of the war, compared to the pre-war period. A forecast is made regarding how the country’s situation and state policies will further affect these flows and shape the balance of payments situation. The results prove that the financial inflows from emigrants have had, and continue to have, a significant impact on the balance of payments, acting as a stabilizing factor against external economic shocks. However, despite the enormous emigration of Ukrainians abroad, the volume of international financial inflows from emigrants has not changed since the beginning of the full-scale war. For the first time, the author proposes policy recommendations for the Government of Ukraine and the National Bank of Ukraine aimed at avoiding adverse balance of payments shocks in the face of declining remittances from emigrants to Ukraine. JEL: F22.